PREDIKSI KEJADIAN PENYAKIT TUBERKULOSIS PARU DI KABUPATEN BIMA TAHUN 2015-2020 - hamdin (Jurnal Kesehatan dan Sains, 2022)
Tuberculosis is an infectious disease caused by bacteria (Mycobacterium tuberculosis) and most often attacks the lungs. Tuberculosis is the leading infectious disease that causes death in the world. About 1.5 million people die every year from TB. The number of TB sufferers is 10 million per year and about 845 thousand of them are in Indonesia. This situation places Indonesia in the third position as the country with the highest TB incidence after India and China. Puskesmas and health human resources as the spearhead of health services, including those who have a high risk of being infected with the corona virus. The aim is to analyze the prediction of the incidence of Tuberculosis. This type of research is descriptive research with a quantitative approach. Research Results The number of cases of tuberculosis patients who were confirmed bacteriologically with AFB (+) and treated in 2015-2020 were 2,257 male cases and 1,314 female cases. Conclusion Prediction of the incidence of pulmonary tuberculosis in 2015-2020 most cases are male, 2015: 375 cases, 2016: 395 cases, 2017: 485 cases 2018: 408 cases, 2019: 451 cases, 2020 : 318 cases.